Anatomy of the coronary arteries in the congenitally corrected transposition of the great arteries - O.V. Stogova; N.M. Rudenko; O.O. Motrechko; D.O. Shypov (Кардіохірургія та інтервенційна кардіологія)
The aim – to investigate the anatomic variants of the coronary arteries (CA) in children with different forms of congenitally corrected transposition of the great arteries (CC-TGA). Materials and methods. 93 children with CC-TGA were observed since January 2007 to December 2017. To determine the anatomy of the coronary arteries coronary angiography was performed in 49 (52 %) patients with different anatomical variants of CC-TGA. Results. The most frequent coronary anatomy was anatomy in which the right coronary artery (RCA) arose the sinus of the right hand (first sinus), and the left coronary artery (LCA) arose the sinus of the left hand (second sinus) and then divided into the left anterior descending artery (LAD) and the circumflex artery (Cx). Anatomy where the origin of coronary arteries from a single sinus was found in 4 (8.1 %) patients: in one patient all arteries arose from the sinus of the left arm, and in the remaining three patients – from the sinus of the right arm. Origin of RCA from LCA (RCA posterior loop anatomy) was found in one patient. Conclusions. Pattern in which the right coronary artery arose the sinus of the right hand (first sinus), and the left coronary artery arose the sinus of the left hand (second sinus) and then divided into the left anterior descending artery and the circumflex artery was the most frequent in patient with CC-TGA. Coronary angiography is of great importance in the preparation to cardiac surgery in patients with CC-TGA due to the variability of the coronary anatomy